3D Printing for a novel Enteric Coated Ibuprofen Tablets - Ahmed Nassar; Yasir Karkar; Ahmed M Faheem (University of Huddersfield Press, 2023)
3D printing has the potential to play a significant role in pharmaceutical research by optimizing medication usage and minimizing adverse effects through the creation of personalised dosage forms. However, various obstacles hinder the full utilisation of this technology to optimise the efficacy of numerous medications such as the quality of tablets, speed of printing etc. Among the various 3D printing techniques, FDM printers combined with HME stand out as one of the most widely used due to their ability to produce high-quality products without the need for organic solvents. Nevertheless, the elevated temperatures required during these processes raise concerns about the stability of the components within the dosage form. Therefore, it becomes crucial to manage various critical factors, particularly the selection of appropriate polymers and drug-release modifiers, to achieve the desired dosage form. To address this, the present study aims to develop novel enteric-coated tablets of ibuprofen using 3D printing technology coupled with hot melt extrusion (HME). Ethyl cellulose is used as the main polymer of the dosage form, Eudragit L 100-55 as a release modifier and Ibuprofen as the active pharmaceutical ingredient (API).